PENGARUH KEPEMILIKAN NPWP, PEMERIKSAAN PAJAK, PENAGIHAN PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN - Dimas Syahrul Saputra; Fatchur Rochman; Herry Purnomo (JAMER : Jurnal Akuntansi Merdeka, 2024)
This study aims to analyze the effect of NPWP Ownership, Tax Audit, Tax Collection and Taxpayer Awareness in increasing Income Tax Revenue. This study uses Quantitative Descriptive research methods. The location of this research and the respondents in this study were offices and employees with a sample of 70 respondents who had NPWP in Sidorejo District, Magetan Regency. The results of hypothesis research show that the independent variable of NPWP ownership is 0.001, the independent variable of tax audit is 0.049, the independent variable of tax collection is 0.040 and the independent variable of taxpayer awareness is 0.041. With these results it can be stated that NPWP ownership, tax audit, tax collection, and taxpayer awareness have a significant effect. Simultaneously, the variables of NPWP ownership, tax audit, tax collection and taxpayer awareness affect the income tax revenue variable.